If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -27 = 4p Reorder the terms: -27 + 3p = 4p Solving -27 + 3p = 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. -27 + 3p + -4p = 4p + -4p Combine like terms: 3p + -4p = -1p -27 + -1p = 4p + -4p Combine like terms: 4p + -4p = 0 -27 + -1p = 0 Add '27' to each side of the equation. -27 + 27 + -1p = 0 + 27 Combine like terms: -27 + 27 = 0 0 + -1p = 0 + 27 -1p = 0 + 27 Combine like terms: 0 + 27 = 27 -1p = 27 Divide each side by '-1'. p = -27 Simplifying p = -27
| S=p-0.3t | | 18n-16(-n-15)=12(n+9) | | (8/5)x=273 | | 22+-k=20 | | 7-8n+48=-97 | | 2(1)-3y=5 | | 5+(x+3)+5+2(x+3)=y | | x+5=2x+22 | | 5=-12 | | 6x+4+5x=81 | | 5=-20 | | x(2x+3)(9)=810 | | 3+f=9 | | 2x+3.25(50)=275 | | 2x-3(0)=5 | | 4n-2(n+2)=2(7n-2) | | 2a-5=27 | | 5x-2(x-5)=-8+5x+14 | | (8/5)+x=273 | | 27=2a-5 | | 4-3x=16+1x | | -3(t-3)+5t=8t-6 | | f+5f=50 | | 2(0)-3y=5 | | 12-4x=9+x | | -5=4+8x-1+3x | | 2x-4(x-5)=-2+3x-3 | | -3(2-r)=4r | | 4-3x=16+1 | | z=121x-241713 | | 12x^2-73x+6=0 | | 7-8(n+6)=-97 |